Incidence of ocratoxin a in coffee production (Horizontes de Enfermería, 2018)
Mycotoxins are substances produced by certain fungi found in foods that are aimed for human and animal consumption. Among the known mycotoxins, the ochratoxin A is the most toxic member, it is nephrotoxic, carcinogenic, hepatotoxic, teratogenic and inmonosuppressive and has been classified by the International Agency for Research against cancer as a possible human renal carcinogen of group 2B. It appears naturally in a wide range of agricultural products. Coffee may be contaminated by ochratoxin A in during harvest, drying and storage of grains. In this work, the factors that cause the presence of ochratoxin A when green coffee is processed, will be made know through a literature review. During the harvest, coffee beans must be harvested directly from the bushes and avoid the collection of overripe, damaged and fallen fruits from the soil because they are a source of contamination, coffes beans should be dried as quickly as possible to take out moisture up to 12% in cement patios to avoid contamination, due to the presence of the fungus in the soil, contact with grains damaged and moisture should be avoided when it is stored because the grain absorbs it. A way to combat the presence of ochratoxin A is to carry out good agricultural practices in the production of coffee, It is important to broadcast the consequences caused by this fungus when it is consumed, in order to take appropriate measures of prevention and control that can be applied along the productive chain.
Keywords: mycotoxins; ochratoxin A; coffee; postharvest; coffee derivatives